How I Got the Story (and Why It Took So Long): Legal History Research in China - Alison W. Conner (Washington University Global Studies Law Review, 2003)
I wanted to write an account of my legal history research in China and the conditions under which I did it; perhaps this is now a kind of legal history too.
Keywords: Legal history; Legal research; China